2019
DOI: 10.1111/ajo.12963
|View full text |Cite
|
Sign up to set email alerts
|

Should antenatal corticosteroids be considered in women with gestational diabetes before planned late gestation caesarean section

Abstract: Babies born to mothers with gestational diabetes mellitus (GDM) are at a greater risk of developing respiratory complications and hypoglycaemia than those born to mothers without diabetes. However, there is currently insufficient evidence as to whether these risks are altered by antenatal corticosteroids after 37 weeks gestation. This retrospective study suggests that antenatal corticosteroids probably reduce respiratory admissions to the newborn intensive care unit with a mild increase in neonatal hypoglycaem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 17 publications
(21 reference statements)
0
17
0
2
Order By: Relevance
“…A retrospective cohort study including 99 neonates whose mother had received antenatal corticosteroids, found that the occurrence of neonatal hypoglycaemia was independent from the time interval between steroid administration and birth 17 . Neonatal hypoglycaemia has also been demonstrated in women with diabetes who have received steroids prior to caesarean birth at term 32 Evidence level 2+ …”
Section: What Are the Risks Associated With The Administration Of Ant...mentioning
confidence: 99%
“…A retrospective cohort study including 99 neonates whose mother had received antenatal corticosteroids, found that the occurrence of neonatal hypoglycaemia was independent from the time interval between steroid administration and birth 17 . Neonatal hypoglycaemia has also been demonstrated in women with diabetes who have received steroids prior to caesarean birth at term 32 Evidence level 2+ …”
Section: What Are the Risks Associated With The Administration Of Ant...mentioning
confidence: 99%
“…The time interval between corticosteroids administration and CS in one study ranged from 1 to 46 days ( 14 ), which may dilute the benefit of ACS treatment given that the optimal intervention timing is when delivery occurs within 2–7 days of administration ( 16 ). The corticosteroids administration timing was not specified in the other study, which found a reduction of respiratory complications ( 15 ). It is unclear whether exposure to ACS at different time points for these early-term infants is beneficial or may lead to some harm.…”
Section: Introductionmentioning
confidence: 96%
“…Whereas, there appears to be insufficient evidence regarding the benefit of ACS in the early term period in pregnancies complicated by diabetes, it is because women with diabetes have largely been excluded ( 13 ), remained unidentified ( 11 ), or were included only in small numbers (6/819 women with GDM) ( 10 ) in studies investigating the efficacy of ACS. Recently, two retrospective studies investigating the efficacy and safety of ACS in women with GDM undergoing a term CS obtained inconsistent findings ( 14 , 15 ). The time interval between corticosteroids administration and CS in one study ranged from 1 to 46 days ( 14 ), which may dilute the benefit of ACS treatment given that the optimal intervention timing is when delivery occurs within 2–7 days of administration ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Em relação às gestantes diabéticas, a discussão se torna ainda mais importante, pois esse grupo apresenta gestações consideradas de alto risco e com maior potencial de desfecho desfavorável para o RN (14) . Essas gestantes estão especialmente vulneráveis às duas principais consequências do uso de corticoide antenatal: hiperglicemia materna e hipoglicemia neonatal.…”
Section: Introductionunclassified
“…Essas gestantes estão especialmente vulneráveis às duas principais consequências do uso de corticoide antenatal: hiperglicemia materna e hipoglicemia neonatal. Portanto, tendo em vista que esse grupo já apresenta maior chance de picos hiperglicêmicos e maior risco para o desenvolvimento de hipoglicemia neonatal (14) devido a condição diabética, o uso de CTC antenatal passa a ser ainda mais criterioso.…”
Section: Introductionunclassified